Efficacy of digital cognitive behavioral therapy for moderate‐to‐severe symptoms of generalized anxiety disorder: A randomized controlled trial. Issue 12 (29th July 2020) - Carl, Jenna R.; Miller, Christopher B.; Henry, Alasdair L.; Davis, Michelle L.; Stott, Richard; Smits, Jasper A. J.; Emsley, Richard; Gu, Jenny; Shin, Olivia; Otto, Michael W.; Craske, Michelle G.; Saunders, Kate E. A.; et al.
Abstract: Background: Cognitive behavioral therapy (CBT) is an efficacious intervention for generalized anxiety disorder (GAD). Digital CBT may provide a scalable means of delivering CBT at a population level. We investigated the efficacy of a novel digital CBT program in those with GAD for outcomes of anxiety, worry, depressive symptoms, sleep difficulty, wellbeing, and participant‐specific quality of life. Methods: This online, two‐arm parallel‐group superiority randomized controlled trial compared digital CBT with waitlist control in 256 participants with moderate‐to‐severe symptoms of GAD. Digital CBT ( Daylight ), was delivered using participants' own smartphones. Online assessments took place at baseline (Week 0; immediately preceding randomization), mid‐intervention (Week 3; from randomization), post‐intervention (Week 6; primary endpoint), and follow‐up (Week 10). Results: Overall, 256 participants were randomized and intention‐to‐treat analysis found Daylight reduced symptoms of anxiety compared with waitlist control at post‐intervention, reflecting a large effect size (adjusted difference [95% CI]: 3.22 [2.14, 4.31], d = 1.08). Significant improvements were found for measures of worry; depressive symptoms, sleep difficulty, wellbeing, and participant‐specific quality of life. Conclusion: Digital CBT ( Daylight ) appears to be safe and efficacious for symptoms of anxiety, worry, and further measures of mental health compared with waitlist control in individuals with GAD.